1969
DOI: 10.1111/j.1151-2916.1969.tb13350.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Surface Energy of Glass

Abstract: Fracture surface energies of six glasses were measured using the double-cantilever cleavage technique. Values ranged from 3.5 to 5.3 J/m2 depending on the chemical composition of the glass and the temperature of the test. The fracture surface energy increased with decreasing temperature and increasing Young's modulus ; however, exceptions to this behavior were noted. The magnitude of the values obtained is discussed with respect to the theoretical strength of glassand possible irreversible effects at the crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
154
4
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(175 citation statements)
references
References 17 publications
15
154
4
2
Order By: Relevance
“…Furthermore, the fracture toughness K Ic of the investigated silica glass was determined by performing fast measurements (displacement ratio of v = 5 µm/s) with notch radii below 12 µm. The obtained fracture toughness is equal to K Ic = 0.82 MPa√m, which matches very well with the value given in the literature [19]. Based on Eq A1 and the pilot test with different notch radii, a reasonable precrack length of l 0 = 15 µm can be assumed for a specimen with a notch radius of r N ≈ 12 µm.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the fracture toughness K Ic of the investigated silica glass was determined by performing fast measurements (displacement ratio of v = 5 µm/s) with notch radii below 12 µm. The obtained fracture toughness is equal to K Ic = 0.82 MPa√m, which matches very well with the value given in the literature [19]. Based on Eq A1 and the pilot test with different notch radii, a reasonable precrack length of l 0 = 15 µm can be assumed for a specimen with a notch radius of r N ≈ 12 µm.…”
Section: Discussionsupporting
confidence: 74%
“…As its value depends only on the type of bond that is being broken, the calculated values for glassy and crystalline silica should be similar. The surface energy of silica glass under N 2 atmosphere and at 300 K is reported (Wiederhorn, 1969) to be approximately 4.4 J m −2 ; while MD simulations ( Leed and Pantano, 2003) yield an area density of Si-O-Si bonds of 7.2 bonds nm −2 , resulting on an activation energy of 360 kJ mol −1 . This is remarkably consistent with monocrystalline α-quartz, with values of 310 and 340 kJ mol −1 [for cracks propagating on the a < 1120 > plane, on directions normal to the planes z < 0111 > and r < 1011 >, respectively] calculated using fracture (Atkinson, 1979;Timms et al, 2010) and bond density data (Bloss and Gibbs, 1963) under inert atmosphere.…”
Section: Application To Experimental Datamentioning
confidence: 99%
“…We have observed that this model adequately describes tensile failure such that the material parameters do not have to be changed for different meshes. The three remaining constants, σ 0 = 0.25GPa, E, and G f = 10J/m 2 are the maximum tensile stress, Young's modulus (computed by the bulk and shear moduli) and the fracture energy per unit area for soda lime glass, which is two times higher than literature values [16]. The results of the simulations corresponding to the drained (dry) impact experiment are shown in Figure 4a and 4b.…”
Section: Continuum Damage Model For An Eulerian Hydrocodementioning
confidence: 51%